Transcriptional coordination of hepatic autophagy by nutrient-sensing nuclear receptor PPARα and FXR - Jae Man Lee (Korean Society of Pediatric Endocrinology, 2016)
Nuclear receptors are in general ligand-dependent transcription factors that control a variety of mammalian physiologies including development, differentiation, proliferation, and homeostasis. Recent studies have found that two nutrient-sensing nuclear receptors, peroxisome proliferator-activated receptor α and farnesoid x receptor, responding to fasting or feeding state, respectively are able to regulate autophagy, an evolutionarily conserved catabolic process involved in lysosomal degradation. In this review, we discuss the role of these nutrient-sensing nuclear receptors in an aspect of transcriptional regulation of autophagy, and how these nuclear receptor-driven transcriptional programs integrate lipophagy, a lipid autophagy with fatty acid oxidation to coordinate hepatic lipid metabolism in the fasted state of the liver.